Transportation-logistic processes of cargo flow treatment improvement at the territory of the river port - Kuzmenko, A. I.; Trofimov, A. V. (Systems and Technologies, 2018)
The potential of Ukrainian river transport is analyzed. The main problems of the present state of river transport are revealed and the prospects of integra-tion of river ports to the European transportation network are considered. An analysis of the current state of Ukrainian river transportation development has shown that the technical support and efficiency of using the resourceful navigable potential of Ukrainian rivers for a long period of time have a negative dynamics. But at the state level, the development of inland waterways is declared as a pri- ority activity of the Ukrainian Ministry of Infrastructure.The deterrent factors of transport-logistic activity development of the river ports are determined. These include: insufficient quantity and high percentage of deterioration of the river fleet; unattractive proposals of logistics and transportation services; insufficient values of transshipment operations time from concurrency point of view, which leads to an unacceptable increase in the cargo delivery time, etc.Possible ways to improve the cargoes transshipment processes from ground types of transport to water and in the opposite direction due to introduction of logistic technologies are offered. Such an approach will provide an opportunity to correctly organize the interaction between different types of transport on the ter-ritory of the river port.The scheme of possible logistic chain time elements for cargo flows treat-ment during the processing in the river port is made. It has been established that river ports is a significant element of cargo delivery logistics system during mixed transportation with the participation of water transport, which, in most cases, de-termine the time component of the whole logistic chain of goods delivery. The re- levant transportation processes have been formalized in order to identify real time reserves by which it is possible to reduce the time during which cargo and vehicles are located at the port during the transfer process from one type of transport to another and to cut the corresponding financial costs.Further research may be concerned to identifying the time reserves for other parts of the mixed cargo delivery logistics systems in order to accelerate the total transportation process and to reduce the total cost of transportation, which will increase the competitiveness of river transport and make it more attractive for organizations and enterprises that are customers of transportation services.